Etnomatematika pada Pola Lantai Tari Jathilan Reog Gembong Bawono - Luthfi Qothrun Nada; Muhammad Hasan Asnawi (PT Cendekia Education Center, 2026)
This study aims to describe the ethnomathematics concept found in the floor pattern of the Jathilan Dance in the Reog Gembong Bawono art form. The study uses a qualitative approach with an ethnographic research type. Data collection techniques were carried out through observation, interviews, and documentation of Reog Gembong Bawono artists in Banyuwangi. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the floor pattern of the Jathilan Dance contains various mathematical concepts, especially transformation geometry and pattern regularity. These concepts include horizontal lines, diagonal lines, translations, rotations, and reflections that are visible in the movement of the dancers and group formations during the performance. In addition, there is regularity and symmetry in the arrangement of movements that reflect aesthetic values ​​and group cohesiveness. This study shows that mathematics is not only present in formal learning, but also lives in community culture through traditional arts. Thus, the floor pattern of the Jathilan Dance can be used as a contextual and innovative source of mathematics learning based on local culture.